ITIL® 4 : Digital and IT Strategy. - Limited, AXELOS. (The Stationery Office Ltd, 2020)
The ITIL 4: Digital and IT Strategy forms one publication of the Higher-Level guidance towards the Strategic Leader designation, following ITIL 4 Foundation.